Occurrence of aflatoxin M1 in pasteurized and UHT milks in China in 2014–2015. (August 2017) - Li, Songli; Min, Li; Wang, Pengpeng; Zhang, Yangdong; Zheng, Nan; Wang, Jiaqi
Abstract: This survey was performed to assess the safety of milk in China, specifically by assessing the presence of aflatoxin M1 (AFM1) residues in pasteurized and ultra high temperature (UHT) milk. In 2014–2015, 193 samples of UHT milk were collected from different cities in China. In 2015, 38 samples of pasteurized milk were collected from different cities in China. AFM1 was detected using an enzyme-linked immunosorbent assay (ELISA). AFM1 positivity was defined as a concentration exceeding the detection limit of the assay (0.005 μg/kg). Other cut-offs that were used were the legal AFM1 limits in the European Union (EU) and China (0.05 and 0.5 μg/kg, respectively). In 2014 and 2015, 88.6% and 59.6% of UHT milk samples were AFM1-positive, respectively. The pasteurized milk samples were less frequently AFM1-positive (47.4%). In 11.9% of the 2014–2015 UHT milk samples, the AFM1 levels exceeded the EU limit. This is lower than the frequency we recorded in 2010 (20.3%). None of the pasteurized milk samples exceeded the EU limit in 2015. The UHT milk samples from the north of China were less likely to be contaminated than the samples from the south in both 2014 and 2015. None of the samples exceeded the Chinese legal limit. Highlights: This survey was performed to assess the presence of AFM1 residues in milk products in China. Only 11.9% of UHT and none of the pasteurized milk samples in China exceeded the EU limit in 2014–2015. The safety of milk products in China has improved in recent years. The UHT milk samples from the north of China were less likely to be contaminated than south.